Psychological capital moderate the influence of job satisfaction on performance - Zhou, Yan-Hong; Gao, Jin-Jin; Chen, Yi-Wen (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2013)
In order to explore the interaction effect of psychological capital and job satisfaction on performance, the concept psychological capital of positive psychology and job satisfaction were used in conceiving a model which was about the moderate effect of psychological capital on performance. An experimental design between subjects was conducted with 321 IT employees. The indications of the results are as follows: (1) older IT employees have better task performance and contextual performance than younger; (2) the higher psychological capital and job satisfaction, the better task performance and contextual performance; (3) psychological capital could moderate the influence of job satisfaction on contextual performance, rather than task performance. In fact, it could improve the satisfaction of employees and the performance of the organization by enhancing the psychological capital.